Thomas Pennant Barton letter with typewritten transcript - Barton, Thomas Pennant, 1803-1869.
Letter. Includes a typewritten transcript.
In part, typewritten transcript.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Diplomats